Elastic properties of perovskite A TiO3 (A=Be, Mg, Ca, Sr, and Ba) and Pb B O3 (B=Ti, Zr, and Hf): First principles calculations - Pandech, Narasak; Sarasamak, Kanoknan; Limpijumnong, Sukit (My University, 2015)
The mechanical properties of perovskite oxides depend on two metal oxide lattices that are intercalated. This provides an opportunity for separate tuning of hardness, Poisson's ratio (transverse expansion in response to the compression), and shear strength. The elastic constants of series of perovskite oxides were studied by first principles approach. Both A-site and B-site cations were systematically varied in order to see their effects on the elastic parameters. To study the effects of A-site cations, we studied the elastic properties of perovskite ATiO3 for A being Be, Mg, Ca, Sr, or Ba, one at a time. Similarly, for B-site cations, we studied the elastic properties of PbBO3 for B being Ti, Zr, or Hf, one at a time. The density functional first principles calculations with local density approximation (LDA) and generalized gradient approximation (GGA) were employed. It is found that the maximum C11 elastic constant is achieved when the atomic size of the cations at A-site and B-site are comparable. We also found that C12 elastic constant is sensitive to B-site cations while C44 elastic constant is more sensitive to A-site cations. Details and explanations for such dependencies are discussed.